2017
DOI: 10.4049/jimmunol.1601686
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Adenosine A2a Receptor Signals Inhibit Germinal Center T Follicular Helper Cell Differentiation during the Primary Response to Vaccination

Abstract: Adenosine A2a receptor (A2aR) signaling acts as a barrier to autoimmunity by promoting anergy, inducing regulatory T cells (Tregs), and inhibiting effector T cells. However, in vivo effects of A2aR signaling on polyclonal CD4 T cells during a primary response to foreign antigen has yet to be determined. To address this problem, we immunized mice with peptide antigen 2W1S coupled to PE in CFA and treated with the selective A2aR agonist CGS-21680 (CGS). 2W1S:I-Ab-specific tetramer-binding CD4 T cells did not bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Purified naive KRN T cells were then adoptively transferred (~10,000 cells per recipient) via tail vein injection into either wild‐type or Tcra −/− F1 host mice to initiate the recognition of the GPI/I‐A g7 self antigen (Figures A–C). Beginning 1 day after adoptive transfer, host mice were given intraperitoneal injections of the selective A2aR agonist CGS twice daily, at a dose of 2.5 mg/kg (Tocris), or with vehicle alone (phosphate buffered saline [PBS]), as previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified naive KRN T cells were then adoptively transferred (~10,000 cells per recipient) via tail vein injection into either wild‐type or Tcra −/− F1 host mice to initiate the recognition of the GPI/I‐A g7 self antigen (Figures A–C). Beginning 1 day after adoptive transfer, host mice were given intraperitoneal injections of the selective A2aR agonist CGS twice daily, at a dose of 2.5 mg/kg (Tocris), or with vehicle alone (phosphate buffered saline [PBS]), as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…Investigations in our laboratory and others have recently determined that A2aR signaling during the primary response to a foreign antigen in strong adjuvant has the ability to divert CD4 T cell differentiation away from the follicular helper T (Tfh) and germinal center (GC)–Tfh cell lineages, and consequently could reduce help for the differentiation of antigen‐specific GC B cells and isotype class–switched plasmablasts . In RA, autoreactive B cells are thought to be induced by Tfh cells to undergo clonal expansion, isotype class–switch recombination, and somatic hypermutation within the GCs, and this ultimately leads to the differentiation of anti–citrullinated protein antibody–secreting plasma cells .…”
Section: Introductionmentioning
confidence: 99%
“…98 Using adoptive cell transfer models, we observed that transferred OVA-specific TCR-transgenic CD4 + T cells from Rag −/− mice (devoid of Foxp3 + Treg cells) into Rag-sufficient mice did not give rise to Tfr cells following OVA-IFA immunization, while OVA-specific TCR-transgenic cells from Rag +/+ mice (with thymic Foxp3 + Treg cells) gave rise to Tfr cells. 109 CTLA-4 has a widely known function in maintaining immune homeostasis and in mediating Treg cell function. Indeed, while OVA-specific TCR-transgenic CD4 + T cells were overrepresented within Tfh cells of OVA-immunized mice (compared to mice immunized with a control protein), OVA-specific Tfr cells were found in the same proportion in the two immunizing conditions.…”
Section: Tfr-cell Antigen Specificitymentioning
confidence: 99%
“…60 [104][105][106][107][108] Curiously, a recent report found that adenosine A2a receptor agonists can limit GC and Tfh cell responses following immunization, suggesting adenosine may indeed be a key mediator of Tfr-cell effector functions in humoral responses. 109 CTLA-4 has a widely known function in maintaining immune homeostasis and in mediating Treg cell function. 53,[110][111][112] Indeed, mice selectively lacking CTLA-4 expression on Treg cells succumbed to spontaneous lymphoproliferation with fatal T-cell-dependent autoimmune disease.…”
Section: Tfr-cell Antigen Specificitymentioning
confidence: 99%
“…11 For antigen-based magnetic enrichment, 2W1S peptide was conjugated either to APC or PE (2Wp:MHCII tetramers) as described. 30,35,36 Immunization Mice were immunized s.c. with 75 μg of either OXY-KLH or unconjugated KLH as control. In studies focusing on analysis of 2W1S-specific T cell populations, mice were immunized s. c. with 25 μg of 2W1S SA-PE.…”
Section: Opioid-based Hapten Synthesis Peptides and Conjugatesmentioning
confidence: 99%